A REVIEW ON TRANSDERMAL DRUG DELIVERY SYSTEM: A NOVEL TOOL FOR IMPROVING BIOAVAILABILITY - S, RAJESWARI; T, PRASANTHI; N, SRILAXMI; T, GAYATHRI (Innovare Journal of Sciences, 2021)
Among all the dosages, oral is the best route of administration for its advantages but due to flow of its demerits like poor bioavailability due to first pass metabolism and unpredictable nature of gastrointestinal absorption. Moreover, oral route is cost prohibitive and inconvenient. Transdermal patches are medicated adhesive patches when it was placed on the skin layer it will deliver the drug into the blood stream through skin layer. To overcome the side effects caused by the oral route, drugs given through transdermal are preferred as transdermal patch. By employing sustained release polymers, transdermal patches can be prepared using solvent casting method. Drug excipients compatibility studies are very important to determine whether the excipients are suitable for that drug or not. These compatibility studies are very important to maintain the stability of dosage form. Evaluation studies are very important to determine the accuracy of dosage form at the same time therapeutic action also. Some of the parameters such as weight variation, physical appearance, drug content, moisture uptake, folding, endurance, swelling study and physical appearance, in vitro dissolution studies, ex vivo studies, and in vivo studies were evaluated.